(3OjhGf GdMcGcs - (3aNQGdOjf CHhHcQ Hf eMeO GdMcGc GdUhajs
(3ChdgG (B:s
(3be agPg WdGFY Gdadb CbHdJ JfJVj Ydi GdZSb eTQbj GdUHGM s
(3BNQgG (B:s
(3jG fOje Gdghi bd jG fOje dGJfGd QJHJj bd dG JfGd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B25s
(3fSNI KGdKIs
(3hJTed GdbUGFO GdMejfjGJ hGdecSQGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B89 s
Keywords: (3GdCOHs